Promotional Communication Strategy of Air Bambu Habiburrahman in Increasing Brand Awareness on Instagram @Airbambu.id - Dilla Rahmatillah; Slamet Parsono (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study analyzes the promotional communication strategy used by Air Bambu Habiburohman through their Instagram account @airbambu.id. The findings show that Air Bambu successfully adapts its communication style to the social and cultural context of its audience, which values sustainability and natural products. The use of casual language helps build emotional closeness and maintain relevance with the target market. Content formats such as aesthetic photos, short videos, and Reels are effectively used to deliver engaging and easily understood promotional messages. Collaborations with micro-influencers who share similar values and have a relevant audience have expanded reach, enhanced credibility, and strengthened the brand image. Additionally, prompt responsiveness and relevant promotional offers help foster customer loyalty and audience engagement. These strategies contribute significantly to building brand awareness and establishing long-term relationships with consumers.